Kinetic analysis of net nitrogen mineralization in soil - Mary, B., author; Paul, Eldor A., author; Juma, N. G., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1984)
Studies were conducted to determine the most suitable mathematical equation and the most appropriate method for calculating the values of the parameters of the equation describing the net N mineralization in soil. The cumulative net N mineralized in two treatments of a 15N labeled soil and five unlabeled Saskatchewan soils showed curvilinear trends that could be fitted to either hyperbolic or first order equations. The kinetic parameters of the hyperbolic equation, 15NH0 (potentially mineralizable N) and Tc (time required for 1/2 NH0 to mineralize) determined by nonlinear least squares (NLLS) yielded the best fit to the data for the labeled soil and had the lowest RMS error. Linear regression (1/N vs 1/t) yielded 15NH0 and Tc values which were markedly different than those obtained with the N vs. N/t and t/N vs. t transformations or those obtained with the NLLS method when all the data were considered. The double reciprocal plot gave undue weight to the initial data points. The 15NH0 estimated by NLLS method accounted for 62 and 72% of the total organic 15N remaining in the two treatments of Weirdale loam soil. The NH0 for Saskatchewan soils ranged from 51 to 429 µg N g−1 soil, while the Tc ranged from 7.3 to 45.8 weeks. The 15NF0 values obtained with the first order equation using NLLS method accounted for 39 to 44% of the total organic 15N remaining in soil. The NF0 values for Saskatchewan soils ranged from 35 to 255 µg N g−1 soil while the values of net mineralization rate constant, k, ranged from 0.036 to 0.164 weeks−1. Both equations accurately predicted the amount of net N mineralized over 14 weeks incubation. However, the estimates of potentially mineralizable N and mineralizable N half-life were dependent upon the model used.
Keywords: NO; soil N supplying capacity; organic N; 15N0; nitrogen mineralization potential